Investigating Multispecies Biofilms on Steel Surfaces in Seawater and Biofilm Inhibition by a Novel, Multifunctional Inhibitor - Tuck, Benjamin (Curtin University, 2022)
Biofilm formation is a global, $multi-billion phenomenon spanning a plethora of stakeholders. This thesis investigates critical fundamental aspects of biofilm formation on steel and evaluates the efficacy of a novel, environmentally sustainable and multifunctional inhibitor compound developed through a broader Australian Research Council Discovery Project collaboration. Focused on sustainable and effective biofilm disruption, results from this thesis are used to expand fundamental knowledge and generate a targeted approach to biofilm mitigation that improves biocide function.